Information system for collecting data on the area of ​​irrigated rice fields at the Jombang district agricultural service - Azzahra, Shafira; Zulfikar, Zulfikar (NEWTON: Networking and Information Technology, 2024)
Irrigation is one of the important elements in agriculture, especially in rice fields. Irrigation makes water more available to plants and can increase yields. Therefore, irrigation efficiency and monitoring are important to support agricultural productivity. Looking at the rapid development of technology utilization, it is also needed to help irrigation managers at the Department of Agriculture to collect data systematically. One of them is creating a data collection system in a more modern way. regarding the case of irrigation managers at the Department of Agriculture who have so far been using manual methods. The purpose of this study is to design an Information System for recording the area of ​​rice field irrigation. The SDLC (System development life cycle) method is used with a Waterfall process model: analysis, design, code generation, testing, and support. This system is created using PHP and MySQL programs, Google Chrome software, XAMPP, and MySQL database. The results of the study show that the designed system can help facilitate data collection on the area of ​​rice field irrigation at the Department of Agriculture, Jombang Regency. Keywords: Information System; Data Collection; Irrigation; waterfall